Efeito de diferentes agonistas de receptores galaninérgicos no núcleo dorsal da rafe de ratos expostos a modelos animais de ansiedade e pânico - Morais, Juliana da Silva (2015)
Galanin (GAL) is a peptide present in the CNS of various mammals, including human being. Three different receptors have been cloned for the GAL, GALR1 and GALR3, inhibitory, and GALR2, excitatory. The distribution of GAL in structures involved in the control of emotions, and behavior studies suggest that GAL may be involved in the neurobiology of anxiety. The effect seems to depend on both the GAL administration site as involved receptor subtype. The dorsal raphe nucleus (DRN) is distinguished by the presence of serotonergic neurons, important to mediate the antidepressant effect of several drugs. About 40% of the neurons of the DRN co-expressing serotonin and GAL. The activation of GALR1 in this structure decreases the firing rate of serotonergic neurons in the DRN. Previous results from our laboratory showed anxiolytic effect of GAL intra-DRN in rats exposed to the elevated T maze (ETM), but no effect on the escape, related to panic. One of the limitations of this model is that the escape (latency to leave the open arm) usually occurs within a few seconds, so that detect panicogenic effect (low latency escape) can be difficult. Thus, one aim of this study was to investigate the effect of intra-DRN rat GAL in another experimental model of panic, electrical stimulation of the dorsal periaqueductal gray matter (DPAG), more sensitive to detect panicogenic effect. Furthermore, given the existence of different subtypes of galaninergic receptors (GALR1 and GALR2) in the DRN with opposite transduction mechanisms, inhibitory and excitatory, respectively, it is possible that activation of GALR1 receptors is responsible for mediating the anxiolytic/panicogenic effect while activation of GALR2 receptors induces anxiogenic/panicolytic effect. Accordingly, we tested this hypothesis using a selective agonist for GALR1 (M617) and a selective agonist for GALR2 (AR-M1896) in the DRN in rats exposed to ETM. The administration of M617 1.0 and 3.0 nmol in the DRN facilitated inhibitory avoidance, suggesting an anxiogenic-like effect., while administration of AR-M1896 3,0nmoles in the DRN impaired the inhibitory avoidance, suggesting an anxiolytic-like effect, both without changing locomotor activity of animals tested in the open field. Also there was no effect of these drugs on the ETM escape behavior. Later, the pre-treatment with WAY100635 was tested in order to verify that administration of a 5-HT1A antagonist would be able to block the effects seen with GALR2 agonist in animals exposed to ETM. The anxiolytic effect of AR-M1896 was attenuated by the prior administration of WAY100635 at a dose of 0,18nmol. Therefore these results suggest a relationship between the observed effect with the AR-M1896, the release of 5-HT and activation of 5-HT1A receptors. And finally, the GAL 0,3nmol intra-DRN increased significantly the jumpping and trotting thresholds of animals submitted to electrical stimulation of the DPAG, suggesting a panicolytic effect. Together, the results show that the GAL in the DRN participates in the mediation of behavioral responses related to anxiety and, less clearly, to Panic Disorder. The results also shows that effect of GAL on anxiety depends galaninergic subtype receptor activated.